Analysis of compliance with wearing hospital gowns and its influencing factors among inpatients in a certain third-grade class-A hospital in Changsha (长沙市某三甲医院住院患者病服穿着依从性及影响因素分析) - HUANG Siting (黄思婷); HAN Huiwu (韩辉武); LI Bingfa (李兵发); ZHANG Jinghui (张京慧) (中西医结合护理)
Objective To investigate the compliance with wearing hospital gown and its influencing factors among inpatients in a certain third-grade class-A hospital in Changsha, and provide reference for improving the quality of basic nursing. Methods Totally 3741 inpatients in a certain third-grade class-A hospital were selected as the research objects. The general information questionnaire and the compliance questionnaire were used to investigate the compliance of patients with wearing hospital gown, and the influencing factors were analyzed. Results Totally 3741 questionnaires were sent out, 3710 questionnaires (99. 17%) were valid for analysis. Totally 1520 patients (40. 97%) reported the poor compliance with wearing hospital gowns. There was a significant difference in compliance with wearing hospital gowns between patients from general departments (60. 53%) and severe departments (39. 47%), female (59. 21%) and male patients (40. 79%), patients aged less than 18 years (54. 62%) and 18 years or older (34. 52%) and patients with junior-high-school or lower education level (59. 87%) and with senior-high-school or higher education level (40. 13%)(P<0. 05, respectively). Multiple regression analysis showed that General Department, female, aged less than 18 years old, with junior-high-school or lower education level were the main influencing factors of poor compliance with wearing hospital gowns. Conclusion The main influencing factors of low wearing rate of hospital gowns were general department, female, aged less than 18 years old, with junior-high-school or lower education level. Nursing managers should improve the nursing service according to address existing problems and meet patients’ demands. (目的 探讨长沙市某三甲医院住院患者病服穿着依从性及影响因素, 旨在为提升医院基础护理质量提供依据。方法 选取2020年10月—2021年12月住院患者3741例为研究对象, 采用患者一般资料调查表及穿病服依从性调查表调查患者穿病服依从性, 并进行影响因素分析。结果 本次发放问卷3741例, 回收有效问卷3710例(99. 17%)。穿病服依从性差的患者1520(40. 97%)例, 普通科室(60. 53%)与重症科室(39. 47%)、女性(59. 21%)与男性(40. 79%)、年龄＜18岁(54. 62%)与年龄≥18岁(34. 52%)、文化程度初中及以下(59. 87%)与文化程度高中及以上(40. 13%)的患者之间病服穿着依从性存在差异(P<0. 05)。多元回归分析结果显示普通科室、女性、年龄＜18岁、初中及以下是患者穿病服依从性差的主要影响因素。结论 该院住院患者病服穿着率低的主要影响因素为普通科室、文化程度较低、18岁以下和女性, 不同科室、文化程度、年龄和性别的患者不愿穿病服的原因存在差异。护理管理者应针对不同原因和患者意愿改良现有病服满足不同患者的需求, 以此提升护理品质。)